The mediating effect of customer trust of E-WOM and online customer reviews impacting purchase decision of household electronic products at a marketplace: evidence from Indonesia - Sudaryanto Sudaryanto; Anifatul Hanim; Ivana Rosediana Dewi; Asila Dwi Kartikasari; Rusdiyanto Rusdiyanto (Cogent Business & Management)
This study aims to evaluate and assess the impact of online customer reviews and electronic word-of-mouth on consumer trust and how these factors influence consumers’ decisions to purchase household electronic products on A marketplace. The study employs a quantitative path analysis methodology. The study population consists of A marketplace users in East Java who have made household electronic purchases on the platform and are at least 17 years old. Purposive sampling was used to obtain the sample, which was collected via questionnaires. Two hundred fifty people responded to the online survey using Google Forms. To test the hypothesis in the research model, respondent data were processed using Structural Equation Modelling Partial Least Squares (SEM-PLS) with SmartPLS software. The findings indicate that consumer trust is greatly influenced by electronic word-of-mouth and online customer reviews, and purchase decisions have a significant impact on consumer trust. The following factors significantly influence purchase decisions: electronic word-of-mouth, online customer reviews, electronic word-of-mouth through consumer trust, and online customer reviews.